2006
DOI: 10.1016/j.visres.2006.01.009
|View full text |Cite
|
Sign up to set email alerts
|

The extent of the dorsal extra-striate deficit in amblyopia

Abstract: Previously, we have shown that humans with amblyopia exhibit deficits for global motion discrimination that cannot be simply ascribed to a reduction in visibility or contrast sensitivity. Deficits exist in the processing of global motion in the fronto-parallel plane that suggest reduced extra-striate function (i.e., MT) in amblyopia. Here, we ask whether such a deficit also exists for rotation and radial components of optic flow that are first processed at higher sites along the dorsal pathway (i.e., MSTd). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 42 publications
6
72
1
Order By: Relevance
“…Under foveal viewing conditions (Fig. 3B, right column), two significant main effects (F (1,12) ¼ 26.97, P < 0.01 for eye of origin and F (2,24) ¼ 156.23, P < 0.01 for temporal frequency, respectively) and a significant interaction were found (F (2,24) ¼ 16.782, P < 0.01). The interaction was due to the higher threshold found in the amblyopic eye at 3 Hz.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Under foveal viewing conditions (Fig. 3B, right column), two significant main effects (F (1,12) ¼ 26.97, P < 0.01 for eye of origin and F (2,24) ¼ 156.23, P < 0.01 for temporal frequency, respectively) and a significant interaction were found (F (2,24) ¼ 16.782, P < 0.01). The interaction was due to the higher threshold found in the amblyopic eye at 3 Hz.…”
Section: Resultsmentioning
confidence: 93%
“…A mblyopia traditionally is thought of in terms of a purely spatial deficit as reflected by reduced acuity, 1 reduced contrast sensitivity, 2,3 spatial distortions/inaccuracy, [4][5][6] and reduced sensitivity for global spatial tasks. [7][8][9][10] However, more recently evidence has emerged for a deficit in amblyopia for global motion 11 including optic flow 12 and for the maximum spatial displacement supporting motion perception for random dot kinematograms (Dmax). [13][14][15] The fact that low level motion performance is thought to be normal in amblyopia 16 raises the question of whether these global motion deficits could be a consequence of the spatial loss in amblyopia.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated significant changes in behaviour and physiology, looking at the interocular ratio of contrast sensitivity and spatial frequency. Furthermore, paediatric clinical populations with motion perception deficits include: dyslexia (Cornelissen et al 1995;Demb et al 1998;Edwards et al 2004), amblyopia (Giaschi et al 1992;Simmers et al 2006), autism (Milne et al 2002) and mental retardation (Fox & Oross, 1990), whereas there is also psychophysical evidence for abnormal magnocellular processing in 6-month-old infants with autism in their families (McCleery et al 2007). Also, Hammarrenger et al (2007)demonstrated using physiology that in very preterm infants (£30 weeks) there was a significant delay in the development of the magnocellular pathway.…”
Section: Perturbations Of Normal Maturationmentioning
confidence: 99%
“…As a second step, these studies have scaled stimuli based on visual acuity and compensated for contrast sensitivity losses to equate the output of early visual cortex from the amblyopic eye to that of normal-vision participants. Despite a nominal match at the level of early visual cortex outputs, patients with amblyopia still show deficits on illusory tilt perception (18), contour integration (19)(20)(21)(22)(23), global motion sensitivity (8,(24)(25)(26)(27)(28), object enumeration (29), and object tracking (7,30). The impairments listed above have been interpreted to indicate that amblyopia may involve abnormalities in "higher-level" (e.g., extrastriate) neural processing that occur independent of any deficits in early processing stages (e.g., in striate cortex).…”
mentioning
confidence: 99%